A Novel Method for L Band SAR Image Segmentation Based on Pulse Coupled Neural Network - Harwikarya, Harwikarya; Rudiarto, Sabar; Sebastian, Glorin (Universitas Dharma Wacana, 2020)
Pulse Coupled Neural Network (PCNN) is claimed as a third generation neural network. PCNN has wide purpose in image processing such as segmentation, feature extraction, sharpening etc. Not like another neural network architecture, PCNN do not need training. The only weaknes point of PCNN is parameter tune due to seven parameters in its five equations. In this research we proposed a novel method for segmentation based on modified PCNN. In order to evaluate the proposed method, we processed L Band Multipolarisation Synthetic Apperture Radar Image. The Results showed all area extracted both by using PCNN and ICM-PCNN from the SAR image are match to the groundtruth. There fore the proposed method is work properly.Copyright © 2017 International Journal of Artificial Intelegence Research.All rights reserved.